Structural Analysis and Redesign of Qalqilya commercial center under static and dynamic loads - Ihab Nazzal (My University, 2023)
This graduation project is the structural analysis and design of The Qalqilya commercial center in the city of Qalqilya in Palestine. The building is consisting of 6 floors with total area equal to 5186 m2. It consists of several facilities such as parking, offices, stores and residential apartments. Starting with studying the soil, the bearing capacity of the site is 350 KN/m2 . The analysis and design of the project was performed on gravity loads (dead, superimposed dead and live) will be studied in graduation project 1 and all loads including seismic loads will be studied in graduation project 2. Also, after studying the geometry and dimensions of the architectural drawings, initial dimensions of horizontal structural elements were calculated taking in consideration the predicted deflections, such that two- way solid slabs of 20 cm thickness are used. one beam sections of 50cm×45 cm was used. Initial dimensions of columns and walls were selected based on the probable axial loads applied. A three-dimensional model was built in ETABS 16.2.1. Loads, load combinations, materials, members, and stiffness properties are all modeled in the program. Before using the model, it was verified for analysis using compatibility, equilibrium, and stress strain checks. The proposed initial dimensions were checked taking in consideration deflections and axial and shear capacities of structural members. Before acceptance of design results from the program, they were undergoing to hand verification processes, such that one beam, one column, and one slab were designed manually, and they were compared result by ETABS. All results were within acceptable range of error.